Sheng-Jiang Powder Ameliorates High Fat Diet Induced Nonalcoholic Fatty Liver Disease via Inhibiting Activation of Akt/mTOR/S6 Pathway in Rats. (4th October 2018) - Li, Juan; Zhu, Lv; Zhang, Yu-mei; Chen, Huan; Miao, Yi-fan; Kang, Hong-xin; Ren, Hong-yu; Wan, Mei-hua; Long, Dan; Tang, Wen-fu
Abstract : Background and Aims . Nonalcoholic fatty liver disease (NAFLD) is an alarming public health problem that directly contributes to increased prevalence of liver cirrhosis and hepatic cell cancer, but without any specific pharmacological option. Sheng-jiang powder (SJP), an empirical Chinese medicine formula to treat NAFLD, showed great efficacy but the specific mechanisms have never been reported. Therefore, we performed this study to explore the effect of SJP on NAFLD and the potential mechanism. Methods . NAFLD was induced by high fat diet (HFD) feeding. Rats were treated with SJP/normal saline daily for 10 weeks and all rats were euthanized after 12 weeks' feeding. Liver tissue samples were obtained for biochemistry test and pathological evaluation. Additionally, oleic acid induced LO2 cells were employed to simulate a cell model of NAFLD. Cells were subjected to western blotting for Akt, mTOR, S6, SREBP1-c, and FASN detection after coincubated with SJP, LY294002 (a selective PI3K inhibitor), or the combination for 24h. Results . HFD significantly induced hepatic steatosis. Plenty of lipid droplets were observed under transmission electron microscope. The ultrastructure of liver cells showed distinct changes with obvious endoplasmic reticulum expansion, mitochondrial contraction, and cell matrix solidification. Although no difference was detected in serum hepatic enzymes and tissue proinflammatory cytokines, the tissue level of SOD and GSH-px was much lower and the pathologic injuries were much severe in HFD feeding rats. However, SJP treatment significantly attenuated the ultrastructure changes and protected rat liver against inflammatory injury. Abundant of lipid droplets and high expression of pAkt, pmTOR, pS6, and FASN were observed in oleic acid treated LO2 cells, while these changes were restored by SJP treatment. Conclusions . SJP is efficient in attenuating HFD induced NAFLD in rats and this effect might be partly related to the inhibition of Akt/mTOR/S6 pathway.